1987
DOI: 10.1039/c39870001659
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of the binuclear complex di-µ-oxo-bis[N,N′-bis(2-methylpyridyl)ethane-1,2-diamine]dimanganese(III,IV)perchlorate trihydrate,[(bispicen)MnO]2(ClO4)3·3H2O

Abstract: The title complex, a new binuclear di-p-oxo complex of manganese-(111) and -(Iv) with a single tetradentate ligand in place of the previously reported bidentate bpy or phen ligands, has been synthesised and characterised by X-ray crysta I I og rap h y and cyclic vo Ita m met ry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
36
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 2 publications
9
36
0
Order By: Relevance
“…(1) 177 The difference between the average MnϪN(axial ligand) distances around both Mn ions reflects the asymmetry in electron distribution between the two Mn ions. [6] Here the value is 0.230 Å , which is comparable to that found for [ Figure 2 in the form of the χ M T versus T plot. was generated by the best fit parameters given in the text χ M T decreases from 0.64 cm 3 mol Ϫ1 K at 292 K to a plateau at 0.38 cm 3 mol Ϫ1 K around 60 K. This is characteristic of an antiferromagnetic coupling between the electronic spins of the Mn(III) and Mn(IV) ions which produces a spin S ϭ 1/2 ground state.…”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…(1) 177 The difference between the average MnϪN(axial ligand) distances around both Mn ions reflects the asymmetry in electron distribution between the two Mn ions. [6] Here the value is 0.230 Å , which is comparable to that found for [ Figure 2 in the form of the χ M T versus T plot. was generated by the best fit parameters given in the text χ M T decreases from 0.64 cm 3 mol Ϫ1 K at 292 K to a plateau at 0.38 cm 3 mol Ϫ1 K around 60 K. This is characteristic of an antiferromagnetic coupling between the electronic spins of the Mn(III) and Mn(IV) ions which produces a spin S ϭ 1/2 ground state.…”
Section: Methodssupporting
confidence: 78%
“…The MnϪMn distance is 2.646(2) Å , which is comparable to the value found in dimanganese(III,IV)-di-µ-oxo complexes previously reported. [6] [12] An antibonding molecular orbital which is half occupied for the Mn(III) ion and empty for the Mn(IV) ion results fom the interaction of the d z 2 orbital with the σ orbitals of the axial pyridine N2 atom and the axial primary amino-group N4 atom. In previous studies it has been found that the average axial Mn(III) primary amine distance is 2.276 Å [9] 2 ] 3ϩ is 2.233 Å .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that during the 3!4 reaction step the carboxylate arms are concomitantly displaced to accommodate the two m-oxo ligands. Thus, an arrangement similar to other, known bis(moxo)-dimanganese complexes of linear N 4 bispicen-based [11] ligands (Mn···Mn = 2.7 ) [12][13][14] is achieved. The anticipated facile oxidation of 3 (oxidase activity) can be invoked to explain the slightly different curve shape in the first evolution step (the front of the peak shows a spike, which indicates an initial rapid reduction in O 2 concentration).…”
mentioning
confidence: 89%
“…Then the sample was immediately put into an EPR tube and frozen quickly to 77 K. UV irradiation was done at 77 K with a 1000 W Hg/Xe lamp (Oriel). 16 In other systems, the Mn-Mn axis is not an axis of symmetry, and the distances around each Mn atoms can be inequivalent as in [Mn 2 O 2 (TPA) 2 ] 3+ where the distances are Mn III -N ax ) 2.260 Å, 2.206 Å and Mn IV -N ax ) 2.012 Å, 2.014 Å. the Mn-Mn axis is a C 2 axis.…”
Section: Nn′-dimethyl-nn′-bis(imidazol-4-ylmethyl)ethane-12-diaminmentioning
confidence: 99%